2014
DOI: 10.5897/ajb2014.13622
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal efficacy of Jatropha curcas L. (Euphorbiaceae) leaf and seed aqueous extracts against Culex pipiens L.

Abstract: Culex mosquitoes play a vital role in transmitting pathogens which continue to have a harmful impact on human beings. Indeed, Innovative vector control strategy like use of plant extracts as alternative sources of insecticidal and larvicidal agents against vector-borne diseases has become unavoidable. In this context, the purpose of the present search was to explore the larvicidal properties of Jatropha curcas L. leaf and seed extracts against Culex pipiens L. The larvicidal activity was evaluated in eight dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…All the test larvae treated with various extracts died after 24 hours of exposure with less concentrations of the extract required to kill the larvae as time of exposure increased. The finding seemed to correlate with the report of Fatnassi et al (2014) who evaluated the larvicidal efficacy of Jatropha curcas leaf and seed aqueous extracts against Culex pipiens and reported 100% and between 60 to 100% mortality for aqueous seed extract and aqueous leaf extract after 24 hours of exposure respectively (Tomass et al, 2011). Kaushiki and Mahesh (2013) who had evaluated the phytochemicals and larvicidal activity of Jatropha curcas seed oil against Aedes aegypti reported that the hexane extract of J. curcas seed oil had highest mortality against the fourth-instar larvae of Aedes aegypti with values LC₅₀= 640 ppm (0.064%) after 24 hours of exposure (Kaushiki and Mahesh, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…All the test larvae treated with various extracts died after 24 hours of exposure with less concentrations of the extract required to kill the larvae as time of exposure increased. The finding seemed to correlate with the report of Fatnassi et al (2014) who evaluated the larvicidal efficacy of Jatropha curcas leaf and seed aqueous extracts against Culex pipiens and reported 100% and between 60 to 100% mortality for aqueous seed extract and aqueous leaf extract after 24 hours of exposure respectively (Tomass et al, 2011). Kaushiki and Mahesh (2013) who had evaluated the phytochemicals and larvicidal activity of Jatropha curcas seed oil against Aedes aegypti reported that the hexane extract of J. curcas seed oil had highest mortality against the fourth-instar larvae of Aedes aegypti with values LC₅₀= 640 ppm (0.064%) after 24 hours of exposure (Kaushiki and Mahesh, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is however not directly in agreement with Tomass et al (2011). In their study, Tomass et al (2011) evaluated the larvicidal effects of Jatropha curcas against Anopheles arabiensis and had reported that crude methanolic extract of J. curcas showed higher larval mortality against third instar larvae of Anopheles arabiensis than that of its column chromatographic fractions (Fatnassi et al, 2014). All the test larvae treated with various extracts died after 24 hours of exposure with less concentrations of the extract required to kill the larvae as time of exposure increased.…”
Section: Discussionmentioning
confidence: 99%
“…This activity is due to its phenolic compounds. The same applies to Fatnassi et al [33] who have worked also on a species belonging to the family Euphorbiaceae (Jatropha curcas L.) and found that the larval activity after 24 h of exposure, 100% mortality for aqueous seed extract. While in our work the organic extracts especially the EtOAc fractions exhibited the best larvicidal activity.…”
Section: Discussionmentioning
confidence: 77%
“…toxicity could be attributed to the presence of many chemical ingredients such as alkaloids, steroids, flavonoids, saponins, tannins and triterpenes. Alkaloids are known to possess medicinal and pesticidal properties (Fatnassi, et al, 2014). These compounds have been reported in all parts of the plant but are more abundant in its seeds (Haas and Mittelbach, 2000).…”
Section: Discussionmentioning
confidence: 99%